Analisis Spasial Tekstur Tanah Terhadap Penilaian Risiko Bencana Hidrometeorologi di Kecamatan Rumbia-Kelara, Kabupaten Jeneponto - Asmita Ahmad; Meutia Farida; Nirmala Juita (Jurnal Wilayah dan Lingkungan, 2022)
Soil texture is one of the keys to answering various soil susceptibility problems to hydrometeorological disasters in South Sulawesi. Some research results show a positive response related to the relationship between soil texture and hydrometeorological natural disasters. However, the spatial analysis of soil texture distribution in an area has not been widely associated with hydrometeorological disasters. This research aims to conduct spatial analysis related to the role of soil texture in hydrometeorological disasters (landslides and flash floods) with a case study in Kelara Watershed, Rumbia-Kelara District, Jeneponto Regency. In the topsoil and subsoil layers, samples were taken by purposive sampling in the Kelara watershed. Texture analysis was carried out using the hydrometer method, the distribution model of the soil texture fraction using the inverse distance weighting method, and the disaster risk assessment using the weighting method with field calculator. The dominant land use in the Kelara watershed is mixed dryland agriculture on a slope class of 25-45%. The dominance of soil texture in the Kelara watershed is the texture of silty clay loam to silty clay. The dominant clay fraction distribution in the upstream part of the Kelara watershed is 37.15-49.71%, so it has a reasonably high soil expansion power and can increase surface runoff. The distribution of silty fraction in the Kelara watershed area is evenly distributed in the upstream and central parts of the Kelara watershed area at 48.49-59.71%, causing the soil to be easily dispersed and triggering landslides-flashfloods. The level of susceptibility to landslide-flash floods in the Kelara watershed area in Jeneponto Regency has a very susceptible class of 63.21% of the total watershed area, which shows the high potential for landslide-flash floods. This potential requires mitigation measures to minimize disaster events and requires firm action from the local and central governments for the protection and utilization of upstream watershed areas in order to be sustainable.